Synthesis, characterization and biological studies of nickel(II) complexes containing thiosemicarbazone and thiourea derivatives / Hana Bashir Mohammed Shawish - Mohammed Shawish, Hana Bashir (2014)
The aim of this study is the preparation of new nickel(II) complexes with N/S donor ligands and their mixed complexes with co-ligands. A number of nickel(II) complexes of thiosemicarbazone derivatives of 2,3-dihydroxybenzaldehyde and thiourea derivatives of diamines have been synthesized and characterized by a combination of spectroscopic studies, elemental analysis, and X-ray crystallography. Five series of nickel(II) complexes with thiosemicarbazone ligands of the type H3L (RCH=NNHC = 2,3-dihyd = H; H3L1, CH3; H3L2, C6H5; H3L3, C2H5; H3L4) have been verified by means of IR, NMR and, in some cases, X-ray crystallography. These five series of nickel(II) thiosemicarbazone complexes have been prepared by using different starting nickel(II) compounds, Ni(ClO4)2.6H2O, [NiCl2(Bpy)], Ni(OAc)2.4H2O, [NiCl2(PPh3)2] and NiCl2 with dppe, giving complexes with the formula [Ni(H3L)(H2L)]ClO4, [Ni(H2L)2][Ni(H3L)2]Cl2, [Ni2(HL)2], ([Ni(H2L)(PPh3)]Cl, [Ni(HL)(PPh3)]) and [Ni2(HL)2(dppe)] respectively. Results from spectroscopic data and crystal structure analysis show that in all complexes the thiosemicarbazone ligands coordinate as tridentate ONS donors in different coordination modes. The complexes [Ni(H3L)(H2L)]ClO4 and [Ni(H2L)][Ni(H3L)]Cl2 are octahedral with two thiosemicarbazone ligands coordinating as neutral H3L and monodeprotonated H2L ligand whereas the complexes [Ni2(HL)2], ([Ni(H2L)(PPh3)]Cl, [Ni(HL)(PPh3)]) and [Ni2(HL)2(dppe)] are square planar with the thiosemicarbazone ligand coordinating as doubly deprotonated HL in [Ni2(HL)2], [Ni(HL)(PPh3)], [Ni2(HL)2(dppe)] and as monodeprotonated H2L in ([Ni(H2L)(PPh3)]Cl. phenyl, o-phenylamine, p-phenylamine and o-aminopyridine) have been prepared and characterized. Thiourea diamine ligands have been coordinated to nickel(II) and the differing binding modes of the ligands in the absence and presence of co-ligands have been investigated. The reaction of the thiourea ligands with nickel(II) salts yields mononuclear diamagnetic complexes with thiourea ligand coordinates as bidentate NS donors, while the reaction of nickel salts with the thiourea ligands in the presence of 1,10-phenanthroline or 2,2'-bipyridine affords binuclear paramagnetic complexes with the thiourea ligands coordinating as tridentate NNS donors. With the aim of evaluating the effect of varying N4 substitution from methyl, ethyl to phenyl in thiosemicarbazone moiety and the coordination environments for nickel complexes with thiosemicarbazones ligands on biological activities, DNA topoisomerase inhibition assay has been carried out. The results from this study showed that the ability of the complex to inhibit the enzyme strengthened as the ligands become more hydrophobic and the coordination environment around the nickel ion is square planar. The gel electrophoresis results of incubating nickel complexes of thiourea as main ligands as well as their mixed complexes with polypyridyl ligands as variable subsidiary ligands showed that all these complexes are able to inhibit the function of topoisomerase enzyme better than the free ligands. In addition, the results suggested that for all complexes the degree of inhibition of the topoisomerase I depended on the concentration of the nickel(II) complexes except for the thiourea series of complexes with p-phenylamine and o-aminopyridine, which are not concentration dependent.